2017
DOI: 10.2174/1871527316666170102120211
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and Protective Roles of Dietary Nrf2 Activators Against Central Nervous System Diseases

Abstract: Central nervous system diseases are major health issues and are often associated with disability or death. Most central nervous system disorders are characterized by high levels of oxidative stress. Nuclear factor erythroid 2 related factor (Nrf2) is known for its ability to regulate the expression of a series of enzymes with antioxidative, prosurvival, and detoxification effects. Under basal conditions, Nrf2 forms a complex with Kelch-like ECH associated protein 1, leading to Nrf2 inactivation via ubiquitinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 162 publications
1
49
0
Order By: Relevance
“…Thus, Nrf2 pathway activation takes place to act against the accumulation of ROS. Consequently, Nrf2 activators have been proposed as antioxidant targets in neurodegenerative and neuropsychiatric disorders (Alzheimer's disease, Parkinson's disease, Huntington's disease, autism, schizophrenia, and depression) to counteract the increase in oxidative stress [138][139][140]. The action mechanisms of the antioxidants used against oxidative stress are shown in Figure 2.…”
Section: Antioxidant Treatment Against Oxidative Stress In Adhdmentioning
confidence: 99%
“…Thus, Nrf2 pathway activation takes place to act against the accumulation of ROS. Consequently, Nrf2 activators have been proposed as antioxidant targets in neurodegenerative and neuropsychiatric disorders (Alzheimer's disease, Parkinson's disease, Huntington's disease, autism, schizophrenia, and depression) to counteract the increase in oxidative stress [138][139][140]. The action mechanisms of the antioxidants used against oxidative stress are shown in Figure 2.…”
Section: Antioxidant Treatment Against Oxidative Stress In Adhdmentioning
confidence: 99%
“…1,11,12 Nrf2 upregulation by Keap1 inhibition has been proposed as a potential therapeutic strategy to target oxidative stress-involved pathologies. 10,[13][14][15] Importantly, Nrf2 activation by genetic knock-out studies and pharmacological Keap1 inhibition has shown encouraging neuroprotective effects in animal models of cerebral ischemia, hemorrhagic stroke, traumatic brain injury, and chronic neurodegenerative disorders. [16][17][18][19][20] An increasingly prevalent strategy to upregulate Nrf2 is to competitively disrupt the protein-protein interaction (PPI) between the Keap1 Kelch domain and the Nrf2 Neh2 peptide motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that heme oxygenase‐1 (HO‐1) is a target site and antioxidant mediator of rosuvastatin in endothelial cells . In recent years, HO‐1 has emerged as an important mediator of antioxidants and has been found to exhibit a central role in cellular antioxidant defense in various tissues including heart, kidney, and neuronal cells . Further, a study revealed that rosuvastatin elicited dose‐dependent delayed protection against excitotoxic stress.…”
Section: Introductionmentioning
confidence: 99%